Re-thinking HIV-Related Stigma in Health Care Settings: A Qualitative Study - Gagnon, Marilou (Journal of the Association of Nurses in AIDS Care, 2015)
People living with HIV (PLWH) continue to endure stigma and discrimination in the context of health care. This paper presents the findings of a qualitative study designed to (a) describe stigmatizing and discriminatory practices in health care settings, and (b) explore both symbolic and structural stigma from the perspectives of PLWH. For the purpose of this qualitative study, 21 semi-structured in-depth interviews were conducted in the province of Quebec, Canada. The data were analyzed following the principles of thematic analysis. During analysis, three themes were identified, and relations between these themes were delineated to reflect the experiences of participants. The findings suggest that HIV-related stigma in health care settings is episodic in nature. The findings also suggest that HIV-related stigma is experienced through interactions with health care providers (symbolic stigma) and, finally, that it is applied systematically to manage risk in the context of health care (structural stigma).
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; inégalités; justice sociale; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle